Demographic characteristics of cladocerans subject to predation by the flatworm Stenostomum leucops - Nandini, S.; Sarma, S. S. S. (Hydrobiologia, 2013)
We present data on the population dynamics and life table demography of four common cladoceran taxa Ceriodaphnia dubia , Ceriodaphnia cornuta , Macrothrix triserialis , and Moina macrocopa at varying densities (0.04 and 0.16 ind ml −1 ) of the predatory flatworm Stenostomum leucops . We also studied the impact of S. leucops on competition between C. dubia , M. triserialis , and M. macrocopa . Experiments, with four replicates for each treatment, were conducted in 200 ml recipients with 50 ml of moderately hard water and the green alga Scenedesmus acutus at a concentration of 0.5 × 10 6 cells ml −1 . We conducted all the experiments with single clones of each taxa. We found that Ceriodaphnia cornuta , regardless of the presence of its beak, was adversely affected to a greater degree than C. dubia due to the presence of the flatworms. Moina macrocopa and Macrothrix triserialis were adversely affected in the competition experiments due to the presence of the flatworms whereas C. dubia was not. The spines of Macrothrix triserialis were not an effective defense against predation by the worms. The population growth rate of Moina macrocopa was significantly higher (0.45 d −1 ) in the presence of S. leucops infochemicals than in controls (0.3 d −1 ).